ALIH KODE DAN CAMPUR KODE DALAM PERCAKAPAN ANTARSISWA SMA NEGERI 1 SUTI SEMARANG KABUPATEN BENGKAYANG - Asista, Vera; Madeten, Sisilya Saman; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study examines the phenomenon of code-switching and code-mixing in the conversations of students at SMA Negeri 1 Suti Semarang, Bengkayang Regency. The background of this research lies in the multilingual environment of the school, where students use various local languages, including Dayak Bakati Sebiha, Bemoyok, and Malay, alongside Indonesian. The study employed a qualitative descriptive approach with data obtained through observation and note-taking of students"™ daily conversations in informal settings. The findings reveal that the only type of code-switching identified is internal code-switching, occurring between languages within the same linguistic family, such as from Dayak Bakati Sebiha to Malay, or from Indonesian to a local language. Furthermore, code-mixing was found exclusively at the word and clause levels, involving the insertion of local language elements into Indonesian or vice versa. These linguistic shifts occur naturally, reflecting students"™ communicative flexibility and their socio-cultural identity. The results suggest that language use among students is influenced by social relationships and communication contexts, highlighting the importance of recognizing and valuing linguistic diversity in educational settings.